Electronic and vibrational properties of the high Tc superconductor Bi2Sr2CaCu2O8: an ab initio study. (23rd April 2021) - Yelpo, Carla; Faccio, Ricardo; Ariosa, Daniel; Favre, Sofía
Abstract: In this work, ab initio calculations were performed in order to study the vibrational spectra of the Bi2 Sr2 CaCu2 O8 (Bi2212) compound. A structural modulation correction on some atomic positions, producing a distorted structure with lower symmetry, is used for the calculation. We argue that this correction allows to account for an average effect of the incommensurate superstructure, generating a more accurate representation of the real unit cell observed in this compound. A complete and conclusive vibrational assignment is performed, discussing the correspondences with previous experimental and theoretical reports. A brief analysis of the electronic density of states and band structure comparing the tetragonal and distorted unit cell is also included.